THE EFFECT OF WORD CHAIN GAME ON STUDENTS’ VOCABULARY MASTERY (AN EXPERIMENTAL STUDY AT SEVENTH GRADE STUDENTS OF SMP NEGERI 1 PANDAN 2017/2018 ACADEMIC YEAR) - tennove melfin lase (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The objectives of this research is to know whether there is a significant effect of word chain game on students’ vocabulary mastery at seventh grade students of SMP Negeri 1 Pandan. This research uses experimental method with pre-experimental research design; one group pre-test post-test design. The population is all of the seventh grade students which consist of 96 students. Technique sampling that used on this research is systematic sampling and the number of the sample consists of 30 students. In collecting the data, the researcher uses observation sheet to get the data of the application of word chain game and test to get the data of the students’ vocabulary mastery. The researcher uses statistic process in analyzing by using t test formula. Based on the data that had been analyzed, the result of data analyzing showed that t count is higher than t table (t count 2.33 > t table 2.04). So, the hypothesis is accepted. It means that there is a significant effect of word chain game on students’ vocabulary mastery at seventh grade students of SMP Negeri 1 Pandan